Does fluid restriction improve outcomes in infants with hypoxic ischemic encephalopathy? A pilot randomized controlled trial. (November 2018) - Tanigasalam, Vasanthan; Plakkal, Nishad; Vishnu Bhat, B.; Chinnakali, Palanivel
Abstract Objective To evaluate whether a strategy of restricted fluid intake in the first 4 days reduces mortality and morbidity among term neonates with moderate to severe hypoxic ischemic encephalopathy (HIE) treated with therapeutic hypothermia. Study design Eighty neonates with HIE were randomized between January 2016 and February 2018 to receive normal fluid intake (n  = 40) or restricted fluid intake (two-third of normal intake;n  = 40) in the first 4 days of life. The primary outcome was a composite of death or major neurodevelopmental disability at 6 months of age. Results The primary outcome occurred in 10 infants (26%) in the fluid-restricted group and 3 infants (8%) in the normal fluid intake group, but the difference was not statistically significant (p  = 0.065). Five infants in the fluid-restricted group had hypoglycemia (p  = 0.055). Conclusion Restricted fluid intake did not reduce the composite outcome of death or neurodevelopmental disability and was associated with a trend toward more hypoglycemia.